2017
DOI: 10.1007/s11655-016-2537-7
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for modern treatment of Parkinson’s disease

Abstract: Parkinson's disease (PD) is a chronic and progressive degenerative disorder of brain commonly seen among the elderly. As conventionally medical therapy is of limited relief and potential side effects, complementary and alternative medicine (CAM) has attracted growing public and professional attention. Therapies such as acupuncture, musical/rhythmic therapy and deep brain stimulation have been gradually proved positively in clinic. In this review, we retrospected the scientifific or evidence-based-medicine adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Traditional Asian medical treatments may have an underlying scientific basis for their treatment of PD ( 24 ). Acupressure, a CAM sensory manipulation, holds potential in the treatment of ON-FOG.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Asian medical treatments may have an underlying scientific basis for their treatment of PD ( 24 ). Acupressure, a CAM sensory manipulation, holds potential in the treatment of ON-FOG.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a retrospective review of the historical role of a number of Chinese herbal medicines in the amelioration of tremor, it was shown that the Shakuyaku-kanzo-to might potentially provide natural treatment for PD. 16 However, its active ingredients and molecular mechanisms are unknown. Paeoniflorin (PF) and glycyrrhetinic acid (GA) are main active phytocompounds of Shakuyaku-kanzo-to.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, traditional Chinese herbs or herbal extracts and non-pharmacological interventions are proven beneficial to patients with neurdegenerative disorders, by exerting antioxidant and anti-inflammatory effects [ 236 , 237 ]. Clinically, several studies showed that acupuncture [ 238 ] and Yang-Xue-Qing-Nao granules [ 239 ] improve sleep quality in PD patients.…”
Section: Therapeutic Strategies For Circadian Dysfunction and Sleep D...mentioning
confidence: 99%